What do the potential recipients of disclosure of OSA say? Perspectives from adolescent residents in Scotland and Chile. (July 2021) - Manrai, Raahat; Alaeddine, Reem; Elorreaga, Grayson; Garrett, Lauren; Guerra, Cristóbal
Abstract: Background: With the increase in internet use, new forms of child victimization like Online Sexual Abuse (OSA) have emerged. Children and adolescents rarely disclose these incidents and most disclosure happens around peers. Objective: This research addresses the perspective of adolescents (not victims of OSA), potential recipients of the disclosure, within the context of disclosure of OSA committed by either adult or peer perpetrators. Methods: The study was performed in two stages. We interviewed adolescents in Scotland and then conducted focus groups with adolescents from Chile. Participants and setting: 51 adolescents (6 from Scotland and 45 from Chile) aged 15–20 years participated. Results: Despite differences in age and cultural contexts, there were similarities in responses. Obstacles of disclosure included lack of clarity of OSA, prior levels of personal vulnerability, and gender factors (stereotypes and stigmatization). On the other hand, the disclosure process would be easier for adolescents with more personal resources (e.g. self-confidence) and when they have a supportive social environment, which includes parents, but especially peers. Conclusion: Disclosure of OSA is considered similar to the disclosure of offline sexual abuse. However, differences such as a lack of clarity regarding the boundaries of the relationships on the Internet, and presence of a generational gap between adolescents and their parents or tutors in the use of internet makes early disclosure of OSA highly challenging. Plans to facilitate disclosure should consider different components: behavioral (risky behaviors), emotional (feelings of fear and shame) and cognitive (lack of information, self-blame, stigma). This should be focused on adolescents, potential recipients of disclosure (parents, authorities and peers) and society, where the prejudices and practices that prevent disclosure begin.